Electrochemical methods of wear resistance deposited on the metal surface. - Стечишин, М.С.; Білик, Ю.М.; Мартинюк, А.В.; Голонжка, В.М. (Problems of Tribology, 2015)
The methods of estimation of cavitacion-erosion wearproofness of thermal diffusion chromic coverage’s and poly-mercomposit coverages are in process described on carbon steel 45 and grey cast-iron of СЧ20. The thermal-diffusion chrome-plating was conducted inpowders untight containers at the temperature of 1100 oС and to time of diffusion 6 hours.Polymercomposit of plated consisted of basis – epoxy resin of ED- 16, and as a filler used mixture o carbides of refractory metals the grittiness of 20 … 100 µm. Got compositions with content of filler 130, 170, 190, 230 and by 270 mass).Tests conducted on setting with a magnetostriction vibrator in a 3% solution of chloride of natrium at the tempera-ture of solution 232 oC.The estimation of cavitacion-erosion wearproofness of thermal-diffusion chromic coverages was estimated after speed of losses mass or volume of plated, but not after the losses of mass. At the same time took off dependence potential-time of realization of cavitacion tests ( ) after that specified time of destruction of carbidic constituent of coverage (time of longevity ) exactness of estimation here rises from  30 min to  1min.At tests polymer of composition coverages the estimation of their longevity was conducted at times general capac-ity of coverage and at times hasp of coverage . The worked out method allows to promote exactness of estimation of wear-proofness, to conduct optimization of thickness, content and ratio of components of filler in plated.